Power, hydro-hegemony and the construction of cooperative transboundary water relations :the case of the incomati international river basin - Zikhali, Thobekile (My University, 2019)
What do transboundary water interactions in the Incomati River Basin tell us about the issues of power and hydro-hegemony in Southern Africa after apartheid? In a water-scarce region such as Southern Africa, a river basin shared by many states presents multifarious socio-political and international relations challenges. The glaring economic and power differentials among the affected riparian countries accentuate such challenges. The thesis's main objective is to explore through Constructivist Institutionalism how socio-political relations constructed around water at a transfrontier level – in this case the Incomati River Basin - intersect with (sub) regional peace and development. The deficiency in the previous studies is failure to explain how states manage to forge cooperative relations despite the ubiquity of power in transboundary water governance. Theoretically, cooperation assumes a realist model of international relations, whereas, in the Incomati River Basin we have transnational cooperation which is more usefully theorized through more complex notions of power, hegemony and an interrogation of the structure and agency debate. I concur with the body of knowledge that acknowledges that the issues of space and time are critical for understanding the evolution of transboundary water relations. However, I argue that in our understanding of space and time, we need to explore the dynamic role of structure and agency. Despite my initial understanding of water being an instantiation of state power, empirical evidence, reveals the opposite. Water is a site of contestation where power represents a triumph of preferences rather than state power. While transboundary water literature perpetuates the question of ‘who gets what when and how’, the current dynamics in the Incomati River Basin have moved to ‘how best do I get the capacity to create what is best for my state’. The study relies on triangulating various methods such as semi-structured interviews, focus group discussions, informal conversations, document analysis, academic literature reviews, and participatory observations to arrive at valid conclusions. The triad of ideas, structure and agency proposed by Constructivist Institutionalism produced four broad lessons about power in the post-apartheid era. These are power that unites-a constructed reality; power that divides- a disempowering mechanism; power that bleeds- shadows of the past; and power that produces- role of individuals and science in transboundary water governance. Concisely, by taking power as an explanandum, my study contributes to the active role played by transboundary water actors in both practice and theory.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy in Political Studies
Keywords: Right to water; Water-supply--International cooperation